Identification of the antioxidant defense genes which may provide enhanced salt tolerance in Oryza sativa L. - Çakır, Bilgin Candar; ATAK, ÇİMEN; ÇELİK, ÖZGE (My University, 2019)
Antioxidative mechanisms are important to protect cells from the hazardous effects of reactive oxygen species (ROS). Salt stress is one of the environmental stress factors that leads to accumulation of ROS at toxic levels. In this study, we analyzed the responses of two rice (Oryza sativa L.) cultivars against NaCl stress at enzymatic and transcriptional levels. In 14day-old-seedlings, different antioxidant enzyme activities were observed. These findings were also supported by transcriptional analyses of the responsible genes. According to the results, Cyt-APX, CAT A, Cyt-GR1 and proline metabolism-related genes were differentially expressed between two rice varieties under different salt concentrations. Their regulational differences cause different salt sensitivities of the varieties. By this study, we provided an insight into understanding of the correlation between antioxidant defence genes and ROS enzymes under salt stress.
Keywords: Oryza sativa L; Salt Stress; Antioxidant Metabolism; Gene Expression